A configurational approach to the investigation of the multiple paths to success of students through mobile phone use behaviors. (August 2015) - Olufadi, Yunusa
Abstract: We addressed two shortcomings in the existing studies that focused on the association between students' academic performance (SAP) and their mobile phone use behaviors (MPUB) in this study by conducting a self-report, student-based cross-sectional study in two Nigerian universities between February and March 2014. We collected the data for the study from 286 students in the two universities using a convenience-based sampling approach. The data were analyzed using fsQCA version 2.0 and hierarchical linear (blocked) regression (HLR). The HLR results reveal that time spent calling on phone was the only significant predictor of SAP out of the seven MPUB variables (addiction, distraction, dependence, multitasking, time spent calling, time spent using social networking sites and perception on the effect of MPUB on SAP) considered. It further revealed that students' hours of study per day explains more of the variations in SAP than their MPUB. More so, none of the MPUB variables individually meets the minimum consistency score of .85, indicating that no single MPUB variable is by itself sufficient to influence SAP. However, implementing the MPUB variables as a configuration reveals that there are three pathways to attaining high academic achievements. The major finding of the present study suggests that combining several MPUB variables may be more effective than focusing on individual MPUB variables when investigating the relationship between SAP and their MPUB. Highlights: fsQCA is applied for the first time to study the relationship between MPUB and SAP. Use of a single MPUB variable is not sufficient to influence SAP. Awareness of the negative effect of MPUB is necessary for students success but not sufficient. Hours of study per day explains more of the variations in SAP than their MPUB.